KERAGAAN DAN HASIL GALUR-GALUR HARAPAN PADI DI LAHAN RAWA PASANG SURUT - Jumakir . (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2015)
The purpose of research to get a few strains of candidate varieties have high yield potential, resistant bath, performance good, age-short being, the main pest and disease resistant, have good quality rice and ready to be released. The research was conducted in rainy season 2012/2013 in the village Bandar Jaya, Rantau Rasau sub District, Tanjung Jabung Timur District, Jambi Province with the typology of land acid sulfate and flooding water C. The 16 treatments consisted of 13 strains and a comparison of three varieties: IR 70 215, PSBRC 68, TDK1-Sub1, B 13159, B 13131, B 13132, B 13144, B 13134, B 13135, B 13136, B 13138, B 13138, B 13143, IR 42, Inpara 2 and IR 64. The results obtained performance good plant growth and equitable. Strains of good and equitable growth is PSBRC 68, TDK1-Sub1, B 13132, B 13135, and B 13136. PSBRC 68 rice strains gave the highest yield 5,67 ha-1and yield strain of the lowest 4,17 t/ha (B 13131). Comparator varieties IR 42, Inpara 2 and IR 64 is 5,84 ha-1, 5,14 ha-1 and 3,37 ha-1. Strains are preferred by farmers has the characteristics of good and equitable growth, disease resistance and high yield. Of the 13 strains of five strains that have acquired these characteristics are PSBRC 68, TDK1-Sub1, B 13134, and B 13135 and B 13136.Keywords: Rice, Potential yield and Tidal swamp land